Middle Ear Cavity Morphology Is Consistent with an Aquatic Origin for Testudines - Willis, K.; Christensen-Dalsgaar, J.; Ketten, Darlene; Carr, C. (Public Library of Science, 2013)
The position of testudines in vertebrate phylogeny is being re-evaluated. At present, testudine morphological and molecular data conflict when reconstructing phylogenetic relationships. Complicating matters, the ecological niche of stem testudines is ambiguous. To understand how turtles have evolved to hear in different environments, we examined middle ear morphology and scaling in most extant families, as well as some extinct species, using 3-dimensional reconstructions from micro magnetic resonance (MR) and submillimeter computed tomography (CT) scans. All families of testudines exhibited a similar shape of the bony structure of the middle ear cavity, with the tympanic disk located on the rostrolateral edge of the cavity. Sea Turtles have additional soft tissue that fills the middle ear cavity to varying degrees. When the middle ear cavity is modeled as an air-filled sphere of the same volume resonating in an underwater sound field, the calculated resonances for the volumes of the middle ear cavities largely fell within testudine hearing ranges. Although there were some differences in morphology, there were no statistically significant differences in the scaling of the volume of the bony middle ear cavity with head size among groups when categorized by phylogeny and ecology. Because the cavity is predicted to resonate underwater within the testudine hearing range, the data support the hypothesis of an aquatic origin for testudines, and function of the middle ear cavity in underwater sound detection.